Bioethical Issues: A Catholic Moral Analysis - Greenlawn, Jim Byrne (Asian Horizons, 2017)
Scaria Kanniyakonil, Bioethical Issues: A Catholic Moral Analysis, Kottayam: OIRSI Publications, 2017. Pages: 344.